Rozliczanie ośrodków odpowiedzialności na bazie metody "koszt plus" - Michalak, Dawid (Responsibility Centres Settlement Based on the Cost Plus Method, 2007)
An internal price based on the cost plus method is, in practice, one of the commonly used centers settlement for responsibility (in domestic circumstances) but it creates lots of difficulties on the level of market data comparability. By undertaking the appropriate assumption for the comparability analysis and the adequate selection of statistical tools there is a possibility to evidence if the price used in the controlled transaction is set within the market range of the cost plus mark-up and, ipso facto, to evidence if the internal price may be acknowledged as the market one. The appliance of gross or net margin to comparison depends on an individual case and comparable data which are the zero reference point to the internal price.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 378-385